Perkembangan hak untuk berdiam diri di Malaysia dari perspektif Akta Pencegahan Rasuah 1997 - Zulazhar Tahir, (Fakulti Undang - Undang, 2005)

(untitled)
In Malaysia, the right to remain silence may be enforced by the accused during the police investigation or at trial. However, Anti-Corruption Act 1997, restricted the application of the right to remain silence. This Act allowed the courts to drawn on adverse inference to the accused who remain silence during investigation. This is the new scenario in our system of criminal justice. The right to remain silence is actually the right that we inherited from common law system. Right to remain silence is the right of the accused and the accused cannot be penalized when exercising this right whether in trial or under investigation. However, the right to remain silence is no longer helpful to the accused when he or she is charged under Anti-Corruption Act 1997. Therefore, this article will discuss the issue of the right to remain silence in Anti-Corruption Act 1997 by referring to the position in Singapore Criminal Procedure Code which has in pari materia provision with Anti-Corruption Act 1997